2019
DOI: 10.15406/frcij.2019.07.00286
|View full text |Cite
|
Sign up to set email alerts
|

Child porn offenders, solicitation offenders and child sexual abusers: what the literature has to say

Abstract: It is important to understand the difference between child molester, pedophile, hebephilic, and ephebophilia. A pedophile has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 229 publications
(777 reference statements)
0
6
0
Order By: Relevance
“…A central point of this review is that the field needs to conduct more rigorous research on child-pornography-exclusive offenders to better understand the risk posed by this subpopulation of sexual offenders (Johnson, 2019). Although several commentators have concluded that the CPORT has been validated (Brankley et al, 2021, p. 53; Savoie et al, 2022, p. 568) and is ready for use (L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A central point of this review is that the field needs to conduct more rigorous research on child-pornography-exclusive offenders to better understand the risk posed by this subpopulation of sexual offenders (Johnson, 2019). Although several commentators have concluded that the CPORT has been validated (Brankley et al, 2021, p. 53; Savoie et al, 2022, p. 568) and is ready for use (L.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have noted that defining recidivism as a new arrest or charge for a sexual offense grossly underestimates the actual rate of reoffense for most sexual offenders (Drury et al, 2020; Johnson, 2019; Scurich & John, 2019). The 2021 USSC stressed that “any research on sex offender recidivism based on reported arrests, including the Commission’s recidivism findings, should be viewed as a conservative measurement of actual recidivism” (p. 69).…”
Section: Discussionmentioning
confidence: 99%
“…This is applicable to any porn, child or adult. Research also supports that the offender's child sexual related fantasies and contact offending behavior (e.g., modus operandi) were related 2,23, Although some offenders interviewed for research studies have made the claim that viewing child pornography prevents them from engaging in contact offending, 33 no empirical studies have been identified supporting those claims (as already discussed in the previous section for question 4). In fact, most of the data is based on self-report by the offender and the offender having no criminal conviction involving sexual contact with children/minors.…”
Section: How Is It Justified That Child Porn Offenders Can Continue Tmentioning
confidence: 94%
“…For more risk factors and areas of concerns, see Johnson. 4 Most sexual offenses against children are vastly undetected and unreported. 20…”
Section: Is Self-report On the Part Of A Child Porn User To Be Believed?mentioning
confidence: 99%
“…Reasons include to develop romantic relationships, expand social networks, enhance popularity and express one’s true self (Shu et al 2017 ; Hance et al 2018 ). Nevertheless, self-disclosures on SM are used to commit blackmail (Johnson 2019 ). Official statistics internationally indicate an increase in SM blackmail (Abdulkareem 2021 ) but the true extent is unknown as official figures under-estimate this activity due to under-reporting (Ahmed et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%